A high stability, hole-conductor-free mixed organic cation pervoskite solar cells based on carbon counter electrode. (10th March 2018) - Liu, Huijing; Fu, Wuyou; Zong, BeiBei; Huang, Liwen; Zhang, Bo; Wang, Shaowei; Guo, Zuan; Bala, Hari; Sun, Guang; Cao, Jianliang; Zhan, Zhanying
Abstract: In this work, hole-conductor-free mixed organic cation perovskite solar cells based on carbon counter electrode were fabricated under air atmosphere with high humidity condition around 50%. The photovoltaic performance of the perovskite solar cells with mixed organic cation perovskite (FA) x (MA)1− x PbI3 by chemical modification the molar ratios x were demonstrated. The light harvesting abilities and crystal morphology could be controlled with x from 0 to 0.4 which resulted in a corresponding diversification of photoelectric properties in perovskite solar cells. Electrical impedance measurements were performed for investigating the electron transport issues in perovskite solar cells with various x . The optimized perovskite solar cells delivered a short-circuit photocurrent density of 21.63 mA/cm 3, open-circuit voltage of 980 mV, fill factor of 0.45 and overall conversion efficiency of 9.53% as x = 0.3. The long-term stability of the optimized perovskite solar cells was exhibited and the overall conversion efficiency retained about 91% after 49 days in air with humidity around 50%. The hole-conductor-free perovskite solar cells based on carbon counter electrode have low-cost and bring a prosperous application foreground in the future photovoltaic community. Graphical abstract: Image 1